Características morfo-anatômicas e bromatológicas de folhas de amoreira em relação às preferências do bicho-da-seda - Okamoto, Fumiko; Rodella, Roberto Antonio [UNESP] (Springer Nature, 2006)
The objective of this work was to evaluate quantitatively the morphological, anatomical and bromatological characteristics of leaves of ten mulberry cultivars, and to establish the preferences shown by the silkworm. The upper (5 th) and median (15 th) leaves were collected taking branch top into account. In order to compare cultivars, multivariate statistic methods of cluster analysis and principal component analysis were used. The cultivars Korin, Calabresa, IZ 5/2 and IZ 15/7 were considered as the most appropriate to feed silkworms, since they presented high percentage values of eaten leaves, due to certain characteristics such as lower crude fiber contents, lower quantity of cystolith and mucilage idioblasts, lower proportions of epidermis and higher quantities of parenchyma, in relation to the other studied cultivars. Cultivars IZ 13/6 and IZ 57/2 were considered as less recommendable. The other cultivars formed an intermediate group, in relation to silkworm preferences.
Mulberry leaf morphological, anatomical and bromatological characteristics in relation to silkworm preferences
Keywords: Morus; Mulberry cultivars; Quantitative analysis; Sericulture